Goal complexity in family firm diversification: Evidence from China. Issue 1 (March 2020) - Dou, Junsheng; Wang, Ning; Su, Emma; Fang, Hanqing; Memili, Esra
Highlights: Family controlled firms have multiple goals, maintaining family control of the firm is the most fundamental (lower-order) goal in the goal hierarchy. Intra-family succession intention and emotional attachment goals are activated only when the owning family has substantial control over the business. Intra-family succession intention and emotional attachment to the business represent contrasting effects on a family firm's diversification, thus highlighting the inconsistent effects of various SEW dimensions on a family firm behavior. Abstract: Drawing upon goal setting theory with a focus on goal hierarchy and goal inconsistency, this study investigates complex relationships among various socioemotional wealth goals in the context of family firm diversification. Using bootstrapping technique, we empirically analyzed a sample of 367 family-owned private firms in China. This study yields two important insights. First, maintaining family control of the firm is the most fundamental ( lower-order ) goal in the goal hierarchy, and intra-family succession intention and emotional attachment goals come into effect only when the owning family has substantial control over the business. Second, intra-family succession intention and emotional attachment have differential ( inconsistent ) effects on a family firm's diversification. This study makes important theoretical contributions to the family business literature by highlighting the complex relationships underlying the various SEW goals. We also provide practical implications for family business advisors and owners.